The Android developer's cookbook building applications with the Android SDK - Schwarz, Ronan (Addison-Wesley, 2013)
Do you want to get started building apps for Android, today's number one mobile platform? Are you already building Android apps but want to get better at it? The Android Developer's Cookbook, Second Edition, brings together all the expert guidance and code you'll need. This edition has been extensively updated to reflect the other Android 4.2.2 releases. You'll find all-new chapters on advanced threading and UI development, in-app billing, push messages, and native development, plus new techniques for everything from accessing NFC hardware to using Google Cloud Messaging. Proven modular recipes take you from the basics all the way to advanced services, helping you to make the most of the newest Android APIs and tools. The authors' fully updated code samples are designed to serve as templates for your own projects and components. You'll learn best-practice techniques for efficiently solving common problems and for avoiding pitfalls throughout the entire development lifecycle. Coverage includes Organizing Android apps and integrating their activities Working efficiently with services, receivers, and alerts Managing threads, including advanced techniques using AsyncTasks and loaders Building robust, intuitive user interfaces Implementing advanced UI features, including Custom Views, animation, accessibility, and large screen support Capturing, playing, and manipulating media Interacting with SMS, websites, and social networks Storing data via SQLite and other methods Integrating in-app billing using Google Play services Managing push messaging with C2DM Leveraging new components and structures for native Android development Efficiently testing and debugging with Android's latest tools and techniques, including LINT code analysis The Android Developer's Cookbook, Second Edition, is all you need to jumpstart any Android project, and create high-value, feature-rich apps that sell.
Includes index. - Print version record
Keywords: Android (Electronic resource); Application software -- Development; Operating systems (Computers); Logiciels d'application; Développement; Systèmes d'exploitation (Ordinateurs); operating systems; Application software; Development